O desenvolvimento das competências sociais no contexto do trabalho voluntário - Brahm, Maitê de Siqueira (Universidade do Vale do Rio dos Sinos, 2015)
The market has been increasingly demanding companies to operate in higher levels ofcomplexity, which leads them to seek alternative means of management. In this context, the Competency Management emerges with an holistic view of the main resources that the organization disposes and includes the development of organizational competenciesat different levels. However, there are still no studies that establish the relation among the different levels of competencies development. In order to deepen the understanding of the levels of competencies, it is necessary to consider that they set up and develop through social practices. Taking this into account, this study aims to identify which social competencies at individual and collective levels are developed in the practice of voluntary work in a Corporate Volunteer Program in a metallurgy company. This is a qualitative, exploratory and descriptive research, developed through the case study method in the company Thyssen Krupp Brazil. Data were collected through semi-structured interviews, focus groups, non-participant observation and document analysis. The main results show that in order to develop social competencies there must be interaction between the individual and collective competencies of individuals. In addition, the competencies that are most representative at individual and group level for volunteering in the case studied were identified. Another finding is that the meaning attributed to volunteer work is relevant, in all individual, collective and business levels as a means to develop these competencies. The results show that the levels of competencies (individual and collective) are deeply related and complementary.
Keywords: Trabalho voluntário; Competências sociais; Competências coletivas; Competências individuais; Interação; Volunteer work; Social skills; Collective competencies; Individual competencies; Interaction; ACCNPQ::Ciências Sociais Aplicadas::Administração